Im positive its false because they dont add up
Option C: 6 is the value of ![b(-10)](https://tex.z-dn.net/?f=b%28-10%29)
Explanation:
The given expression is ![b(x)=|x+4|](https://tex.z-dn.net/?f=b%28x%29%3D%7Cx%2B4%7C)
We need to determine the value of ![b(-10)](https://tex.z-dn.net/?f=b%28-10%29)
To find the value of
, let us substitute
in the given expression.
Thus, substituting
in the expression, we have,
![b(-10)=|-10+4|](https://tex.z-dn.net/?f=b%28-10%29%3D%7C-10%2B4%7C)
Adding the terms, we get,
![b(-10)=|-6|](https://tex.z-dn.net/?f=b%28-10%29%3D%7C-6%7C)
Since, we know the absolute rule that
and the simplified expression is of the form
, let us apply the absolute rule in the simplified expression.
Thus, we have,
![b(-10)=6](https://tex.z-dn.net/?f=b%28-10%29%3D6)
Thus, the value of
is 6.
Hence, Option C is the correct answer.
Step-by-step explanation:
the answer is regular octagon
i think
Answer: x=9
Step-by-step explanation: rewrite the given equation with y=6, 2x + 3(6)=36
Now simplify 2x +18=36
Subtract 18 from both sides of the equal
2x=18
Now divide both sides by 2 and your answer is x=9
Answer:
c
Step-by-step explanation: